Synthesis and imido-group exchange reactions of tert-butylimidotitanium complexes - Blake, A; Collier, P; Dunn, S; Li, W; Mountford, P; Shishkin, O (1997)
Treatment of TiCl4 with ButNH2 (6 equivalents) followed by addition of bpy (2 equivalents, 4-/er/-butylpyridine) or pyridine (py) (2 or 4 equivalents) afforded the five- or six-co-ordinate /erf-butylimido complexes [ri(NBut)Cl2(bpy)2] or [Ti(NBut)Cl2(py)n] ( = 2 or 3) respectively in good yields. Reaction of rri(NBu')Cl2(py)3] with RNH2 gave the corresponding arylimido derivatives [Ti(NR)Cl2(py)3] (R = Ph, C6H4Me-4, C6H4NO2-4, C6HjMe2-2,6 or C6H3Pr'2-2,6). Addition of tmen or pmdien to [Ti(NBu')Cl2(py)J (n = 2 or 3 respectively) gave the corresponding bi- or tri-dentate amine complexes, [Ti(NBu')Cl2(tmen)] or [TXNBu'JCl2(pmdien)] (tmen = Me2NCH2CH2NMe2, pmdien = N,N,N′,N″,N″-pentamethyldiethylenetriamine). Complexes labelled have been crystallographically characterised.